On some model reduction approaches for simulations of processes in Li-ion battery - Iliev, Oleg; Latz, Arnulf; Zauch, Jochen; Zhang, Shiquan (Proceedings of the Conference Algoritmy, 2015)
In this work, some model reduction approaches for performing simulations with a pseudo-2D model of Li-ion battery are presented. A full pseudo-2D model of processes in Li-ion batteries is presented following [1], and three methods to reduce the order of the full model are considered. These are: i) directly reduce the model order using proper orthogonal decomposition, ii) using fractional time step discretization in order to solve the equations in decoupled way, and iii) reformulation approaches for the diusion in the solid phase. Combinations of above methods are also considered. Results from numerical simulations are presented, and the efficiency and the accuracy of the model reduction approaches are discussed.